The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1002/hed.26572
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic thyroid carcinoma to the parapharyngeal and retropharyngeal spaces: Systematic review with seven newly reported cases describing an uncommon presentation of a common disease

Abstract: Background: Metastatic thyroid carcinoma to retropharyngeal and parapharyngeal (RP/PP) lymph nodes is rare. Literature suggests previous lateral neck dissection (LND) may alter patterns of lymphatic drainage in the neck, predisposing to these less common sites of spread. Methods: PRISMA-guided systematic search for all published cases detailing RP/PP metastases of well-differentiated thyroid carcinoma from 1970 to 2019. Results: Seventy articles were identified and 44 were included, along with seven cases trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(34 citation statements)
references
References 30 publications
6
28
0
Order By: Relevance
“…Computed topography and MRI are the most frequently used imaging techniques to reach the diagnosis. 3,7 The minimal size for detection of LN metastases in this area by CT/ MRI is significantly smaller than the minimal size for clinical detection. 3 CT/MRI are also helpful in defining the extent of the tumor, its relationship with surrounding structures, its compartment of origin (prestyloid vs poststyloid), and might even suggest its histologic nature.…”
Section: Discussionmentioning
confidence: 96%
See 4 more Smart Citations
“…Computed topography and MRI are the most frequently used imaging techniques to reach the diagnosis. 3,7 The minimal size for detection of LN metastases in this area by CT/ MRI is significantly smaller than the minimal size for clinical detection. 3 CT/MRI are also helpful in defining the extent of the tumor, its relationship with surrounding structures, its compartment of origin (prestyloid vs poststyloid), and might even suggest its histologic nature.…”
Section: Discussionmentioning
confidence: 96%
“…2 Studies have shown that .4% to 5% of patients with PTC can develop metastases in the retropharyngeal and the PPS. 3 These locations are associated with a younger age, a more aggressive disease, and a poorer prognosis. 3 A lymphatic vessel from the upper pole of the thyroid gland to the retropharyngeal lymphatic system has been described by Rouviere.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations